Treatment of glioblastoma with re-purposed renin-angiotensin system modulators: Results of a phase I clinical trial. (January 2022) - O'Rawe, Michael; Wickremesekera, Agadha C.; Pandey, Ramesh; Young, David; Sim, Dalice; FitzJohn, Trevor; Burgess, Carl; Kaye, Andrew H; Tan, Swee T.
Highlights: Glioblastoma stem cells express renin-angiotensin system (RAS) and its bypass loops. Patients with glioblastoma are treated with a combination of RAS modulators. The treatment was well tolerated with low side-effects. The treatment preserves the quality of life and performance status of the patients. The treatment may lengthen survival time. Abstract: Glioblastoma is the most common and most aggressive primary brain cancer in adults. Standard treatment of glioblastoma consisting of maximal safe resection, adjuvant radiotherapy and chemotherapy with temozolomide, results in an overall median survival of 14.6 months. The aggressive nature of glioblastoma has been attributed to the presence of glioblastoma stem cells which express components of the renin-angiotensin system (RAS). This phase I clinical trial investigated the tolerability and efficacy of a treatment targeting the RAS and its converging pathways in patients with glioblastoma. Patients who had relapsed following standard treatment of glioblastoma who met the trial criteria were commenced on dose-escalated oral RAS modulators (propranolol, aliskiren, cilazapril, celecoxib, curcumin with piperine, aspirin, and metformin). Of the 17 patients who were enrolled, ten completed full dose-escalation of the treatment. The overall median survival was 19.9 (95% CI:14.1–25.7) months. Serial FET-PET/CTs showed a reduction in both tumor volume and uptake in one patient, an increase in tumor uptake in nine patients with decreased (n = 1), unchanged (n = 1) and increased (n = 7) tumor volume, in the ten patients who had completed full dose-escalation of the treatment. Two patients experienced mild side effects and all patients had preservation of quality of life and performance status during the treatment. There is a trend towards increased survival by 5.3 months although it was not statistically significant. These encouraging results warrant further clinical trials on this potential novel, well-tolerated and cost-effective therapeutic option for patients with glioblastoma.